2007
DOI: 10.1002/ejic.200700436
|View full text |Cite
|
Sign up to set email alerts
|

Combined Studies on the Surface Coordination Chemistry of Benzotriazole at the Copper Electrode by Direct Electrochemical Synthesis and Surface‐Enhanced Raman Spectroscopy

Abstract: The surface coordination chemistry of benzotriazole (BTAH) on a Cu electrode was investigated by electrochemical synthesis of surface complexes and in situ electrochemical surface-enhanced Raman spectroscopy (SERS) in nonaqueous solution. Two different surface complexes were prepared in solution with or without triphenylphosphane (PPh 3 ). A new mixed-valence Cu-N cluster compound containing BTAH was synthesized by direct electrochemical oxidation of Cu in nonaqueous solutions with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…The selected Raman bands and assignments are listed in Table 1 together with the main SERS bands. [24,57] For the free [BMIM]Br liquids, the intensity of the band assigned to the ring stretching mode at about 1353 cm −1 was similar to that of band at 1421 cm −1 . Therefore, the observation of different relative intensities of different vibrational modes presented additional evidence that the signal was due to the adsorbed ionic liquid molecules.…”
Section: Raman Intensitymentioning
confidence: 87%
See 1 more Smart Citation
“…The selected Raman bands and assignments are listed in Table 1 together with the main SERS bands. [24,57] For the free [BMIM]Br liquids, the intensity of the band assigned to the ring stretching mode at about 1353 cm −1 was similar to that of band at 1421 cm −1 . Therefore, the observation of different relative intensities of different vibrational modes presented additional evidence that the signal was due to the adsorbed ionic liquid molecules.…”
Section: Raman Intensitymentioning
confidence: 87%
“…A similar effect was observed by Cater et al in the adsorption of NMIM on Ag electrode. [57] Recently, Santos et al [24] moved the applied potential to −3.0 V (vs Pt) and observed an abnormal enhancement of the relevant bands of [BMIM]PF 6 , which was contributed by the reduction of cation to form BMIM carbine. They also observed an increase in SERS intensity on negative movement of the potential from −0.6 V. Unfortunately, a similar change was not observed for the adsorption of [BMIM]Br at the same potential region in the present case.…”
Section: Raman Intensitymentioning
confidence: 99%
“…Rubim et al proposed the surface complex of Cu and BTAH with the polymer-like structure of (CuBTA) n based on the in situ surface enhanced Raman spectroscopic (SERS) studies [17]. In our previous studies of the interaction of BTAH with Cu electrode in aqueous and non-aqueous system, the structure of the complex with the similar composition as the (CuBTA) n [18]. Although the inhibition mechanism(s) of BTAH on Cu surface was quite clear in the aqueous solution, the efficiency of inhibition was influenced by several factors, such as the concentration, surroundings, the The complexes of benzotriazole (BTAH) with Ag, Cu, Fe, Zn and Ni were prepared respectively in the nonaqueous solution by the direct electrochemical synthesis and characterized by microanalysis and normal Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 97%
“…The coexistence of I À in the solution containing BTAH makes the inhibition efficiency for both anodic and cathodic processes become even more remarkable [19,20], thus indicating the existence of a synergetic effect between I À and benzotriazole on the inhibition. Recently, we reported that some organic ligands might play a negative role in the inhibition when it coexists with BTAH [18]. For example, the introduction of ligands such as b-diketonate, triphenylphosphine (pph 3 ) can result in a remarkable difference in the structure of metal complexes with BTAH, i.e., transform the mononuclear complex to multi-nuclear complex resulting in the different processes of the surface coordination chemistry of BTAH, and thus the inhibition efficiency decreased dramatically [3,5,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation